Boosting Engagement and Reducing Anxiety: The Impact of Quizizz on Science Learning in Elementary Classrooms - Husain, Andi Musthafa; Maryani, Ika; Fauzia, Safira Nur; Hartanto, Dody; Muarifah, Alif (Journal of Pedagogy and Education Science, 2025)
Science education in elementary schools often encounters challenges related to technological accessibility, particularly when integrating digital tools such as Quizizz for assessment. Institutional policies, including restrictions on mobile phone usage, are typically implemented to maintain student concentration and prevent technological distractions. While shifting students' mindset toward new learning methods can be challenging, school support can foster a high-quality learning environment that benefits all students. This study aims to explore the implementation and impact of the Quizizz game on students' anxiety levels during elementary science evaluations. Using a quantitative quasi-experimental design with a Pretest-Posttest Control Group approach, data were collected through questionnaires involving all 43 sixth-grade students. The results indicate that the use of Quizizz as a learning evaluation tool significantly improved student engagement in the experimental group. Overall, 52% of the experimental group fell into the "Moderate" anxiety category, compared to 73% in the control group. The analysis also revealed a significant difference in anxiety levels between the two groups, demonstrating that Quizizz effectively reduces student anxiety during evaluations. These findings highlight the potential of Quizizz as an innovative tool to enhance learning experiences and lower anxiety in classroom assessments.